Cyber Hygiene Maturity Assessment Framework for Smart Grid Scenarios - Skarga-Bandurova, Inna; Kotsiuba, Igor; Velasco, Erkuden Rios (Frontiers in Computer Science, 2021)
Cyber hygiene is a relatively new paradigm is premised on the idea that organizations and stakeholders are able to achieve additional robustness and overall cybersecurity posture by implementing and following sound security practices. It is a preventive approach entailing high organizational culture for information and cybersecurity to enhance security, resilience and protect sensitive data. In an attempt to achieve high resilience of smart grids against negative impacts due to known, unknown, predictable, unpredictable, uncertain and unexpected threats and keep entities safe, the Secure and PrivatE smArt gRid (SPEAR) project has created an organization-wide cyber-hygiene policy and developed a Cyber Hygiene Maturity Assessment Framework (CHMF). This paper presents the assessment framework for evaluation of Cyber Hygiene Level (CHL) in relation to the smart grids. Complementary to the SPEAR Cyber Hygiene Maturity Model (CHMM), we propose a self-assessment methodology based on a questionnaire for smart grid cyber hygiene practices evaluation. The result of the assessment can be used as a health check to define countermeasures and to reapprove cyber hygiene rules as well as security standards and specifications adopted by the Smart Grid operator organization. The proposed methodology is one example of a resilient approach to cybersecurity. It can be applied for the assessment of the cyber hygiene level of Smart Grids end-users and their organization in the context of the good practices in cyber hygiene.